Peran Perawat pada Pasien Sepsis di Unit Critical Care: A Narrative Review - Regina Saragih Turnip; Nur Fadilla Bahri; Irmawati Irmawati; Mashudi Mashudi; Amelia Ganefianty; Ismail Fahmi (FORIKES, 2022)
Sepsis is a medical emergency that describes the body's systemic immunological response to infectious processes that can lead to end-stage organ dysfunction and death. The role of nurses in tackling sepsis patients is critical to identifying the initial condition of sepsis and reducing the continuation of even more severe sepsis. This narrative review aims to identify the role of nurses in treating sepsis patients in critical care units. This research method was the narrative review by analyzing online search databases namely Pubmed, Google Scholar, and Science Direct. The search inclusion criteria were an English-language article, published in 2008-2021, full text, the keywords used were